Biogenic Synthesis of Zinc Nanoparticles, Their Applications, and Toxicity Prospects - Rani, Simran; Kumar, Pradeep; Dahiya, Priyanka; Dang, Amita Suneja; Suneja, Pooja (Frontiers in Microbiology, 2022)
Nanofertilizers effectively deliver the micronutrients and reduce phytotoxicity and environmental risks. Zinc is the essential micronutrient for chloroplast development, activation of certain enzymes and metabolism of primary metabolites. Nano-Zinc oxide (ZnO) is the most widely used Zinc nanoparticle. Concerns regarding the toxicity of conventional physical and chemical methods have generated the need for green approach involving biogenic synthesis of metallic nanoparticles through plants and microorganisms. Microbe-mediated biogenic synthesis of metallic nanoparticles is a bottom-up approach in which the functional biomolecules of microbial supernatant reduce the metal ions into metal nanoparticles. This review discusses the biological synthesis of Nano-ZnO from microorganisms and related aspects such as mechanism of synthesis, factors affecting, methods of application, role in conferring drought stress tolerance and challenges of their synthesis.